Mortality and neurological outcomes in extremely and very preterm infants born to mothers with hypertensive disorders of pregnancy - Noriyuki Nakamura (Nature Portfolio, 2021)
Abstract To evaluate the impact of maternal hypertensive disorders of pregnancy (HDP) on mortality and neurological outcomes in extremely and very preterm infants using a nationwide neonatal database in Japan. This population-based retrospective study was based on an analysis of data collected by the Neonatal Research Network of Japan from 2003 to 2015 of neonates weighing 1,500 g or less at birth, between 22 and 31 weeks’ gestation. A total of 21,659 infants were randomly divided into two groups, HDP (n = 4,584) and non-HDP (n = 4,584), at a ratio of 1:1 after stratification by four factors including maternal age, parity, weeks of gestation, and year of delivery. Short-term (neonatal period) and medium-term (3 years of age) mortality and neurological outcomes were compared between the two groups by logistic regression analyses. In univariate analysis, HDP was associated with an increased risk for in-hospital death (crude odds ratio [OR], 1.31; 95% confidence interval, 1.04–1.63) and a decreased risk for severe intraventricular haemorrhage (0.68; 0.53–0.87) and periventricular leukomalacia (0.60; 0.48–0.77). In multivariate analysis, HDP was significantly associated with a lower risk for in-hospital death (adjusted OR, 0.61; 0.47–0.80), severe intraventricular haemorrhage (0.47; 0.35–0.63), periventricular leukomalacia (0.59; 0.45–0.78), neonatal seizures (0.40; 0.28–0.57) and cerebral palsy (0.70; 0.52–0.95) at 3 years after adjustment for covariates including birth weight. These results were consistent with those of additional analyses, which excluded cases with histological chorioamnionitis and which divided the infants into two subgroups (22–27 gestational weeks and 28–31 gestational weeks). Maternal HDP was associated with an increased risk for in-hospital death without adjusting for covariates, but it was also associated with a lower risk for mortality and adverse neurological outcomes in extremely and very preterm infants if all covariates except HDP were identical.